Enhanced drug metabolism in cigarette smokers. Issue 6028 (17th July 1976) - Hart, P; Farrell, G C; Cooksley, W G; Powell, L W
Abstract : The effect of cigarette smoking on salivary antipyrine disappearance rate, and as an index of hepatic drug metabolism, was studied in 42 healthy subjects. Antipyrine half life was significantly shorter in smokers compared with non-smokers. To determine whether this difference was due solely to tobacco consumption eight subjects were restudied two months after they stopped smoking. The mean antipyrine disappearance rate in this group increased by 23% in contrast to that of a control group, which did not alter. Cigarette smoking contributes to the considerable variation in interindividual rates of drug metabolism.